A Counterfeit Solution for Pharma Supply Chain - Soundarya K.; Priyanka Pandey; R. Dhanalakshmi (EAI Endorsed Transactions on Cloud Systems, 2018)
This paper provides a detailed overview of the blockchain technology and how it can be used to build a foolproof system in eliminating counterfeit products in pharmaceutical industries. Study by various reports indicate that counterfeit products entering the mainstream supply is by far one of the major issue faced by the pharmaceutical industries. By using blockchain across the whole value chain, various pitfalls and challenges faced by the stakeholders can be resolved as blockchain, by design is (i) robust, (ii) improves transparency, (iii) immutable, (iv) authentic, (v) reliable and (vi) secure. Overall, this paper attempts to provide a roadmap on how blockchain transactions can help various stakeholders improve the counterfeit situation, challenges one might face in implementing a blockchain solution and steps for further research.